1997
DOI: 10.1295/polymj.29.607
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide-Silica Hybrid Materials Based on p-Aminophenyltrimethoxysilane Terminated Poly(amic acid)s

Abstract: ABSTRACT:Polyimide-silica hybrid materials with covalently bound phases were prepared via a sol-gel process. The starting materials were p-aminophenyltrimethoxysilane terminated poly(amic acid)s of controlled molecular weight ranging from 5000 to 10000 g mo! -1 and tetramethoxysilane. Optical transparency of the final films increases with the number of bonds between phases. The dependence of the thermal and mechanical properties and morphology on the silica content and/or concentration of bonds between phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…This was attributed to the enhanced compatibility of the two phases, since the epoxy group of the GPTMOS reacted with the acid group of PAA, resulting in chemical bonding between the two phases. Wang, 21,22 Schrotter, 23 Sysel, 24 Chen, 25 and Chang 26 and their coworkers in their separate studies prepared bonded PI-silica hybrids using amino substituted alkoxysilane, for example, aminophenyl-trimethoxysilane (APTMOS), aminoethylaminomethylphenethyltrimethoxysilane, aminopropyl-trimethoxysilane, and aminopropylmethyl-diethoxysilane, and diaminopropyltetramethyl-disiloxane and diaminophenyltetramethyl-disiloxane. They found that both the amino and alkoxy groups on these silanes enable chemical bonding between organic and inorganic networks, resulting in the formation of more homogeneous and transparent films as compared to those prepared using only TEOS.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the enhanced compatibility of the two phases, since the epoxy group of the GPTMOS reacted with the acid group of PAA, resulting in chemical bonding between the two phases. Wang, 21,22 Schrotter, 23 Sysel, 24 Chen, 25 and Chang 26 and their coworkers in their separate studies prepared bonded PI-silica hybrids using amino substituted alkoxysilane, for example, aminophenyl-trimethoxysilane (APTMOS), aminoethylaminomethylphenethyltrimethoxysilane, aminopropyl-trimethoxysilane, and aminopropylmethyl-diethoxysilane, and diaminopropyltetramethyl-disiloxane and diaminophenyltetramethyl-disiloxane. They found that both the amino and alkoxy groups on these silanes enable chemical bonding between organic and inorganic networks, resulting in the formation of more homogeneous and transparent films as compared to those prepared using only TEOS.…”
Section: Introductionmentioning
confidence: 99%
“…3, 4 Sysel pointed out that there are only physical interactions between the organic and inorganic phases in common PI-SiO 2 hybrids, 5 so the size distribution of the second phase was not homogeneous over the hybrid film.…”
Section: Introductionmentioning
confidence: 99%
“…8 -14 The second creates bonding sites between the polymer backbone and the silica. [15][16][17][18][19] A nanoscale polyimide-silica hybrid for fine-line metallization has been reported. 8 Nandi et al 9 produced polyimide-silica hybrids by mixing solutions of pyromellitic anhydride, diaminodiphenyl ether, and silicon tetraalkoxides.…”
Section: Introductionmentioning
confidence: 99%